The prevalence of foot-and-mouth disease in Asia - Aslam, Munazza; Alkheraije, Khalid A. (Frontiers in Veterinary Science, 2023)
Foot-and-mouth disease (FMD) is listed among the highly contagious diseases in animals and is endemic throughout the Asian continent. The disease is caused by the Foot-and-mouth disease virus (FMDV) and affects a wide variety of domesticated animals as well as wild ungulates. Clinically, the disease is described as a vesicular lesion on the tongue, muzzle, lips, gum, dental pad, interdigital cleft, coronary band, and heel of the foot. Sometimes these lesions give rise to lameness. Mastitis is also caused due to teat lesions. A biochemical test reveals that during FMD infection, there are elevated levels of interleukin-1 (IL-1), tumor necrosis factor-alpha, interferon-gamma (IFN-γ), interleukin-6, serum amyloid A protein, lactoferrin, mannose-binding lectin, and monocytes chemo-attractant protein-1 in the serum of infected animals. There is no specific treatment for FMD although some antivirals are given as prophylaxis and antibiotics are given to prevent secondary bacterial infection. This review presents comprehensive data on the prevalence of FMD and serotypes of FMDV that are attributable to the cause of FMD from a regional point of view. It also explains the worldwide dynamics of the seven serotypes of FMD and tries to identify epidemiological clusters of FMD in various geographical areas. Furthermore, the pathology associated with the foot and mouth disease virus along with the pathophysiology is discussed. The continent-wide prevalence and diversity patterns of FMD suggest that there is a need for stringent policies and legislation implementation regarding research and development aimed at manufacturing strain-specific vaccination, infection prevention, and control of the disease.